Plant Physiological Responses to Nutrient Solution: An Overview - Baron, Daniel; Amaro, Amanda C.E. [UNESP]; Campos, Felipe G. [UNESP]; Boaro, Carmen S.F. [UNESP]; Ferreira, Gisela [UNESP] (Elsevier, 2018)
Being sessile, plants developed adaptive and flexible strategies for nutrient acquisition. Localized deficiency or oversupply of many nutrients induces morphological and physiological adaptations, such as gas exchange, ionic accumulation, as well as plant growth and development. Knowledge about the growth dynamics of plant species cultivated in hydroponic systems favors their management, ensuring good development, which reflects positively on the productivity and optimization of natural resources sustainably. The use of nutrient solutions is intended to provide conditions conducive for physiological processes to occur with maximum efficiency. Mineral nutrient solutions provided as hydroponics to plants is used as a tool to study several physiological mechanisms in higher plants and to solve a wide range of problems, including reducing soil and groundwater contamination. The study of plant metabolomics provides valuable insights into the changes that occur in the biochemical mechanisms, in response to environmental factors that the cultivated plants are exposed to. This chapter discusses how recent advances of some physiological effects may be used to understand the role of plant nutrients, besides the management of nutrient solution composition to accomplish these tasks. As future perspectives, the authors of this review encourage new studies on the physiological effects of the availability of different essential mineral elements using other plant species not considered model plants, because we believe that this type of progress is crucial for the advances in the understanding of plant physiology.
Keywords: Hydroponic; Ionic concentration; Leaf gas exchange; Mineral nutrient; Physiological indexes; Plant growth; Plant physiology